KONSTRUKSI HUKUM TERKAIT KEDUDUKAN ANAK HASIL SURROGATE MOTHER DI INDONESIA - Anindya Ratri Widyadari (2023)
Healthy fertility conditions are not always owned by women to get offspring, with the development of the times one way that can be taken is to do a surrogate mother by means of fertilization in someone's womb called a Surrogate Mother. The Surrogate Mother practice is a transaction between the Surrogate Mother and a married couple who requires the role of the Surrogate Mother by using her womb, and the husband and wife give the agreed reward. Given the restrictive Health Law and its application which is carried out only based on agreements and the absence of strict regulations regarding Surrogate Mothers, this research will discuss the opportunities for implementing Surrogate Mothers in Indonesia and the legal position of children from Surrogate Mothers in Indonesia compared to India. This writing uses a type of normative juridical legal research by examining library materials or secondary data. There are no existing laws and regulations in Indonesia that specifically provide permits for the implementation of surrogacy practices, as well as permits to become surrogate mothers, so it is unlikely that surrogacy will be implemented in Indonesia, besides that there are differences between Indonesian and Indian regulations regarding children born to surrogate mothers in Indonesia is not considered a biological child so that it affects position and inheritance. It is necessary to form a law as a legal umbrella that regulates the practice of surrogacy in Indonesia.